RANTES and Chemotactic Activity in Synovial Fluids From Patients With Rheumatoid Arthritis and Osteoarthritis - Joanna Stanczyk; Marek L. Kowalski; Janina Grzegorczyk; Barbara Szkudlinska; Marzanna Jarzebska; Marek Marciniak; Marek Synder (Hindawi Limited, 2005)
A massive accumulation of inflammatory cells in synovial tissues is a major pathological feature of rheumatoid arthritis (RA). Neutrophiles dominate synovial fluid while rheumatoid synovium is infiltrated with mononuclear cells. Mechanisms regulating influx of particular subpopulations of leukocytes into articular cavity and synovium compartment are not completely defined. An increasing amount of data supports a crucial role of a C-C chemokine RANTES in the RA pathogenesis. Our objective is to evaluate chemotactic activity for neutrophils (NCA), lymphocytes (LCA), and monocytes (MoCA) in SFs obtained from patients with RA and osteoarthritis (OA). We also aimed to characterise the relation between chemotactic activity, RANTES, and percentage distribution of leukocytes in SF. SFs from 11 patients with RA and 6 with OA were included in the study. Modified microchamber Boyden method was employed to assess chemotactic activity. Cytological and biochemical analysis of SF was performed. RANTES was measured with ELISA. Rheumatoid SFs were rich in cells with predominance of neutrophiles while osteoarthritic fluids were lymphocytic. RA SFs were also characterised by increased lactoferrin level. Both NCA and LCA were higher in SF from patients with RA (62±12 and 24±6 cells/HPF, resp) as compared to patients with OA (23±6; P<.05 and 6±2 cells/HPF; P<0.05). The chemoattractive effect of RA SF was more pronounced on neutrophiles than on lymphocytes. RA SF expressed high RANTES levels (145±36pg/mL), while OA SF was characterised by only trace amount of this chemokine (2±1 pg/mL). We found positive correlation of RANTES with chemotactic activity for mononuclear cells (LCA+MoCA; R=0.61; P<.05). Surprisingly, RANTES correlated also positively with neutrophiles number (R=0.77; P<0.001). Rheumatoid SF possesses strong chemotactic potency for leukocytes. RANTES is overexpressed in RA SF and is a potential mediator influencing intensity and composition of cellular infiltration in joints affected with inflammatory arthritis.